The Problems of the Omnibus Law in the Employment Cluster Related to Licensing to Hire Foreign Workers - Try Wahyu Widanarti (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2021)
This paper aims to analyze the omnibus law's problems in the labor cluster related to permits to employ foreign workers. Where in the development of legal products in new normal era, after the issuance of the Omnibus Law. One of them is the omnibus law in the employment cluster in the licensing sector for foreign workers. Previously, permits for foreign workers were regulated in Law number 13 of 2013 concerning Manpower and also regulated in Law number 6 of 2011 concerning Immigration with certain limitations in managing permits for foreign workers. The investors who have invested in a certain period in Indonesia will receive facilities in the form of a visa permit process. Concerning the workforce copyright law, which uses the concept of the omnibus law, which currently is the right answer to increasing economic growth in the context of the welfare of the Indonesian nation, however, what is still a problem is the application of the omnibus law concept, the public's view of the ease of licensing foreign workers in The omnibus law provides benefits for foreign investors only because basically the ease of licensing for foreign workers into the omnibus law is intended to accelerate investment.